Effects of Rice Husk Ash on Durability of Self-Compacting Concrete Made with Cassava Peel Ash - Abdulwahab, M. T.; Uche, O. A. U.; Aboshio, A.; Mohammed, A.; Suleiman, A.; Auwal, A. M.; Chidawa, S. U. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
Self-compacting concrete (SCC) is a highly flowable concrete with improved strength and surface smoothness. The preparation of SCC requires high amount of cement. This utilizes tremendous amount of energy and releases carbon dioxide into the atmosphere. It is critical to reduce CO2 emissions during Portland cement (PC) manufacture by partially replacing cement in the SCC. This study evaluates the durability characteristics of SCC produced using cassava peel ash (CPA) combined with rice husk ash (RHA) at 5, 10, 15, 20, and 25 percent cement replacement levels respectively. The effects of water absorption, H2SO4 attack, MgSO4 attack, and high heat on SCC made with CPA and RHA blends were examined. The results show that, as CPA and RHA proportions rise by approximately 5% CPA and 10% CPA+RHA substitution, SCC compressive strength equates to design strength (grade 35). It was also discovered that CPA and RHA both enhance resistance to H2SO4 and MgSO4 degradation, but perform poorly when exposed to elevated temperatures when compared to the control specimen. However, when CPA is utilized with RHA in SCC, the rate of water absorption is reduced to a minimum due to an enhanced pore structure of the CPA-SCC specimen. Generally, a 5% CPA content is considered as the optimum replacement of cement for self-compacting concrete with grade 35.